Assessing the Paradiplomacy of Regional Governments in Indonesia: The Case of Banten Province - Syuryansyah, Syuryansyah (Papua Journal of Diplomacy and International Relations, 2024)
The development of international cooperation has undergone dynamic evolution, with active involvement from local governments that extends beyond the central government's authority. For this purpose, paradiplomacy has been widely applied by local governments in Indonesia. However, several, including the Province of Banten, have not fully optimized its implementation. Despite having significant potential for participating in international cooperation, the execution of paradiplomacy in Banten has not yet reached the expected level. This research aims to explain the implementation of paradiplomacy in the Province of Banten and to identify the factors influencing its ineffectiveness. The research applies a qualitative descriptive approach and uses case studies and document analysis to gain an in-depth understanding of paradiplomacy implementation. Data collection involves library research and field observations. The research finds that two factors contribute to the ineffectiveness of paradiplomacy in Banten, including legal ambiguities in the regulations governing paradiplomacy and the absence of a multi-level paradiplomacy system in Banten. Revitalizing these factors can enhance the effectiveness of Banten’s paradiplomacy. KEYWORDS Paradiplomacy; Soft Power; Sub-state governments